2014
DOI: 10.1186/1471-2253-14-29
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Cisatracurium in different age groups, using a closed loop computer controlled system

Abstract: BackgroundWe devised this study to quantify the effect of age on the consumption of cisatracurium under general anaesthesia, using a computer controlled closed loop infusion system. We further investigated this effect on, sufentanil and propofol consumption.Methods74 patients of physical status I and II, requiring general anaesthesia for elective abdominal surgery, were assigned to three groups. Patients in group 1 were aged from 20 to 45, group 2 were from 46 to 64, and group 3 above 65 years old. General Ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, Joomye et al [ 20 ] studied cisatracurium consumption and recovery index by age group—20–45, 46–64 and ≥ 65 years—and there were significant differences between the groups aged 20–45 and ≥ 65 years, likely because of the reduced body fluid that accompanies aging and that results in increased serum blood drug concentrations and increased volume of distribution due to increased body fat; the authors of that study suggested that the elderly require less cisatracurium to achieve a desirable effect. Although those authors reached their conclusion using consumption and recovery indexes with a closed-loop computer-controlled infusion, we investigated the cisatracurium ED and onset time with a single bolus.…”
Section: Discussionmentioning
confidence: 99%
“…However, Joomye et al [ 20 ] studied cisatracurium consumption and recovery index by age group—20–45, 46–64 and ≥ 65 years—and there were significant differences between the groups aged 20–45 and ≥ 65 years, likely because of the reduced body fluid that accompanies aging and that results in increased serum blood drug concentrations and increased volume of distribution due to increased body fat; the authors of that study suggested that the elderly require less cisatracurium to achieve a desirable effect. Although those authors reached their conclusion using consumption and recovery indexes with a closed-loop computer-controlled infusion, we investigated the cisatracurium ED and onset time with a single bolus.…”
Section: Discussionmentioning
confidence: 99%
“…Although interindividual variability of block duration in response to benzylisoquinoline muscle relaxants is thought to have no clinical significance, a study performed by Joomy et al [35] seems to contradict this belief. The authors used a closed feedback loop devised to control cisatracurium administration with electromyographic response of the muscle.…”
Section: Benzylisoquinoline Derivativesmentioning
confidence: 96%